Exploring the Potential of Virtual Reality (VR) in Developing Students' Thinking Skills: A Narrative Review of the Last Five Years - Faresta, Rangga Alif; Nicholas, Teo Zhao Ser Bryan; Chi, Yixuan; Sinambela, Indah Astri Natalia; Mopoliu, Abdul Ziqron (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2024)
Addressing the persistent issue of inadequate critical thinking skills among students, this study examines the potential of Virtual Reality (VR) to transform educational practices. Traditional teaching methods often prioritize rote memorization, limiting opportunities for higher-order cognitive processes such as analysis, synthesis, and evaluation. This narrative review synthesizes findings from the past five years, focusing on VR’s ability to enhance thinking skills. Employing a systematic literature search via Scopus, 24 reviewed studies were analyzed, highlighting VR’s immersive and interactive capabilities in fostering critical thinking, problem-solving, and engagement. Results indicate that VR surpasses traditional methods by offering experiential learning scenarios, promoting collaboration, and addressing diverse educational needs. Applications in STEM and professional education demonstrate improved cognitive outcomes, including spatial reasoning, decision-making, and retention of abstract concepts. However, challenges such as high costs, infrastructural constraints, and teacher training gaps hinder widespread adoption. Ethical considerations around data privacy and inclusivity further underscore the need for strategic implementation. This study concludes that VR holds transformative potential in education, provided challenges are addressed through targeted investments, interdisciplinary innovations, and inclusive practices. Future research should emphasize long-term studies and integrate emerging technologies like AI and AR to maximize VR’s impact on cognitive skill development.